0.0004
0.004
0.04
0.4
Answer:To solve the equation log3x - log3(x - 8) = 2, we can use the properties of logarithms to simplify and solve for x.
First, let's apply the quotient rule of logarithms. The quotient rule states that log(base a)(b) - log(base a)(c) = log(base a)(b/c).
Using this rule, we can rewrite the equation as log3(x / (x - 8)) = 2.
Next, let's rewrite 2 as a logarithm. The logarithmic form of 2 is log(base a)(b) = c, where a^c = b. In this case, a^c = 3^2 = 9. Therefore, we can rewrite the equation as log3(x / (x - 8)) = log3(9).
Now that the bases are the same, we can set the arguments of the logarithms equal to each other. Therefore, x / (x - 8) = 9.
To solve for x, we can multiply both sides of the equation by (x - 8) to eliminate the fraction. This gives us x = 9(x - 8).
Expanding the right side of the equation, we get x = 9x - 72.
Next, we can subtract 9x from both sides of the equation to isolate x. This gives us -8x = -72.
Dividing both sides of the equation by -8, we find that x = 9.
Therefore, the solution to the equation log3x - log3(x - 8) = 2 is x = 9.
Step-by-step explanation:
Answer:k=37.5 ; xy=37.5
Step-by-step explanation:
Answer:
To put the equation 14x = 6y - 12 into slope-intercept form (y = mx + b), where m represents the slope and b represents the y-intercept, we need to isolate the y variable on one side of the equation.
Starting with 14x = 6y - 12, we can rearrange the equation as follows:
6y = 14x + 12
Dividing both sides of the equation by 6, we get:
y = (14/6)x + 2
Simplifying further, the equation can be written in slope-intercept form as:
y = (7/3)x + 2
So, the equation 14x = 6y - 12, in slope-intercept form, is y = (7/3)x + 2.